The Extension Services and the Level of Productivity of Sugarcane Farmers in the Visayas, Philippines - Oñal, Jr., Paulino A; Jinon, Rex J.; Martinez, Lloyd B. (Future Science / FSH-PH Publications, 2022)
Agricultural extension has been an essential strength in agricultural development and social innovation factor. The word “extension” in the modern meaning was first used which refers to informal public education in England in the second half of the 19th century (Demiryurek, 2014). This descriptive method of research aid at determining the effectivity of extension services and the productivity of sugarcane farmers in the Visayas, Philippines. The 400 sugarcane farmers randomly identified at the 10 locations in the Visayas area of the Philippines. An instrument used was the agency Extension Program Guidelines that measures productivity of the farmers, farm profile and extent of services, among others. The result shows that the level of productivity of sugarcane farms in the Visayas area was high and a significant difference indicates on the level of productivity of sugarcane farms when grouped as to location. The level of productivity of sugarcane farming in the Visayas in terms of indicators such as size of farm, type of soil, land topography, average rainfall received, distance of the farm to the sugar mill, farming innovations, workers’ availability and expenses per hectare was at low productivity. Significant difference in the productivity of sugarcane farming at the different locations in the Visayas area in terms of size of farm, land topography, distance of the farm to the sugar mill, farming innovations, workers’ availability, and expenses per hectare except for the type of soil and average rainfall. The extent of services does not significantly related to the productivity. Relatively, there is no significant relationship existed between the extent of services and farm profile. Farm profile does not influence the level of productivity, too.